Physical health, emotional exhaustion and perceived financial wellbeing: An exploration of Malaysian gen Y employee - Kamaruzaman M.S.; Jaaffar A.H. (Mattingley Publishing, 2023)
Decision making; Finance; Health; Service industry; Surveys; Tourism industry; Decision makers; Emotional exhaustion; Financial service; Online questionnaire; Physical health; Services sectors; Tourism sectors; Well being; Behavioral research